Odpowiedzi

2009-12-01T18:32:51+01:00
A)
4x+5y=12,3
3x-2y= -4

4x+5y=12,3
-2y = -4-3x / :(-2)

4x+5y=12,3
y= 2+ 3/2x

4x + 5(2+ 3/2x) = 12,3
4x+10+7,5x = 12,3
11,5x=12,3-10
11,5x=2,3 /:11,5
x= 0,2

y= 2+ 3/2x
y=2+ 3/2 * 1/5
y= 2+0,3
y= 2,3

x=0,2
y=2,3

B)

3x-0,2y=35
2,5x-5y=5

3x-0,2y=35
2,5x= 5+5y /:2,5

3x-0,2y=35
x= 2 + 2,5y

3(2+2,5y) - 0,2y = 35
6+7,5y-0,2y=35
7,3y=29 /:7,3
y=3,97

x= 2+2,5y
x= 2 + 2,5*3,97
x= 11,93
2 3 2
2009-12-01T22:54:39+01:00
A)
4x+5y=12,3
3x-2y= -4

4x+5y=12,3
-2y = -4-3x / :(-2)

4x+5y=12,3
y= 3/2x+2

4x + 5(3/2x+2 ) = 12,3
y= 3/2x+2

4x+7,5x+10 = 12,3
y= 3/2x+2

11,5x=12,3-10
y= 3/2x+2

11,5x=2,3 /:11,5
y= 3/2x+2

x= 0,2=2/10=1/5
y= 3/2x+2

x= 1/5
y=3/2 * 1/5+2

x= 1/5
y= 0,3+2

x=1/5=0,2
y=2,3

B)

3x-0,2y=35
2,5x-5y=5

3x-0,2y=35
2,5x= 5+5y /:2,5

3x-0,2y=35
x= 2 + 2y

3(2+2y) - 0,2y = 35
x= 2 + 2y

6+6y-0,2y=35
x= 2 + 2y

5,8y=29/:5,8
x= 2+2y

y=5
x=2+10=12